Finale: Contextualising Participation in a Transition Society - Cairns, David; Allaste, Airi-Alina (Studies of Transition States and Societies, 2016)
This special issue of Studies of Transition States and Societies closes with a concluding discussion that aims to contextualise some of the key findings from the preceding articles. To do so, we use comparative level evidence drawn from other regions included in the MYPLACE consortium, identifyng contrasts and commonalities in how youth politics is practiced across different European regions. The basic approach is one of assessing the extent to which patterns of participation in Estonia diverge from activism elsewhere, thus locating Estonian youth within a broader analytical framework.